(untitled) (Al-Qamar, 2022)
Islam came with the liberation of man from all restrictions and shackles. Freedom was one of the legitimate purposes and the basic principles established by Islam. There is no way to a real life without freedom, and it’s the right of the single and society. With pride, dignity, security and safety, equality, justice, chastity and purity. Islam in its legislation laid the foundations and principles of freedom. It freed man from the captivity of lusts, and from the shackles of ignorance, and freed the mind from materialistic philosophies, destructive sects, and man-made religions and from the forms of freedom that Islam granted to man: freedom of belief, expression, opinion, freedom of speech, Issuing the decision, freedom of litigation and complaint, freedom of movement, and among the manifestations of freedom according to the Holy Prophet ﷺ is the freedom to pardon where forgiveness was dearer to him than punishment. There are lessons of the freedom to pardon when one is able, following the example of the Messenger of Allah Almighty Muhammad ﷺ, as the Prophet, raised the Companions in the highest degrees of freedom, the most sublime of its meanings, and the most informed of its goals.